Preliminary investigation of flash sintering of SiC - Zapata-Solvas, E; Bonilla, S; Wilshaw, P; Todd, R (2013)
The feasibility of flash sintering a covalent ceramic, SiC, has been investigated for the first time. Flash sintering involves the application of an electrical potential difference across a powder compact during heating, which leads to sintering at low furnace temperatures in a few seconds and has only been demonstrated with ionic ceramics previously. Near-theoretical density was achieved using Al2O3+Y2O3 sintering aids at a furnace temperature of only 1170°C and in a time of 150s. Specimen temperatures were significantly higher than the furnace temperature owing to Joule heating and consequently heat loss limited densification in the near surface region. It was not possible to reach high densities using "ABC" sintering aids (aluminium-boron-carbon) or pure SiC. The mechanisms involved and potential commercial advantages are briefly discussed. © 2013 Elsevier Ltd.